Kajian Terhadap Istilah Monogenēs dalam Injil Yohanes - Putra, Adi (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2023)
This research explores whether the expression monogenes represents the meaning of a child, an only child, or whether it is intended to emphasize begotten children. This topic is important to research because errors in understanding the meaning of the expression monogenes will have implications for understanding Christology. The term monogenes has generated much debate. The most prominent discussion is whether this expression wants to emphasize only or only begotten. Therefore, the author seeks to find the answer through this research. The method used is a literature study focusing on the term monogenes used in the Gospel of John. The research results show that the term monogenes in the Gospel of John emphasizes the exclusive relationship between Jesus Christ and God the Father where this relationship does not have to be in the framework of a metaphysical relationship or begotten relationship - because that is not what the term monogenes wants to emphasize - but rather the specificity of that relationship later. At the same time, he noted that Jesus was essentially the same as the Father. The explanation above is based on the realization that the term monogenes does not come from the word genna but from the word genos.